Far-Field Reconstruction from Transient Near-Field Measurement Using Cylindrical Modal Development - R. Rammal; M. Lalande; E. Martinod; N. Feix; M. Jouvet; J. Andrieu; B. Jecko (International Journal of Antennas and Propagation)
The aim of this work is to get far field radiation patterns for any radiating source from transient acquisition, in a large frequency range. An outdoor transient Ultra-Wideband near-field measurement base will be installed, a single time pulse radiated by the source will cover the desired spectrum, and the accurate determination of far field radiations will be accomplished by means of cylindrical waves' modal development. This method uses simplified test equipments, easy to be installed, and it reduces measurement costs.